PENERAPAN STRATEGI BELAJAR PETA KONSEP (CONCEPT MAPPING) UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS IV SEKOLAH DASAR - Asril Asril (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the lack of a student learning outcomes can be seen from the results of four gradestudents studied 72 Harapan Baru Elementary School, with an average value of 68. Therefore, the researchersprovide an alternative to the application of the concept map learning strategy in the fourth grade 72 HarapanBaru. This research aims to improve learning outcomes PKn Elementary School four grade students Mandausub 72 Harapan Baru with learning Implementation Strategy Concept Maps. This research is a form ofclassroom action research (PTK) with 2 cycles. Based on research data anlisis after implementing learningstrategies Concept Map, the average percentage of the activity of teachers in the first cycle 66,66% increased to87,46% in the second cycle. The average percentage of student activity also increased, namely 56,25% in thefirst cycle increased to 83,33% in the second cycle. Student learning outcomes in basic score by the averagevalue of 68 and the first cycle increased with an average value of 71,25 class with an increasing percentage oflearning outcomes 4,77% and the percentage of students who completed 65%, and the second cycle increasedagain by an average of 75.50 with the percentage improvement class learning outcomes 11,02% and thepercentage of students who completed 80%. These results indicate that the application of learning strategiesconcept maps can enhance learning outcomes PKn four grade students of SD Negeri 72 Harapan Baru.